Anti-Intellectualism in U.S. Schools - Aimee Howley; Edwina D. Pendarvis; Craig B. Howley (Arizona State University, 1993)
In this essay we present an argument about the relationship between schools' intellectual mission and their role in advancing social justice. In providing an argument of this sort, we claim neither to present a comprehensive review of literature nor to analyze specific educational policies. Rather, we bring together findings about certain features of schools in the United States that we believe contribute to their anti-intellectualism. This examination allows us to tell a story about schools that we think needs to be told; and it also elaborates a frame of reference from which to reconsider schools' mission and practice. Reframing these bases of schooling may be a necessary prelude to educational policies that promote both intellectual and egalitarian outcomes.